The comprehensive agrarian reform program after 30 years: Accomplishments and forward options - Marife Magno-Ballesteros; Jenica Ancheta; Tatum Ramos (Philippine Institute for Development Studies (PIDS), 2017)
This study evaluates the performance of the Comprehensive Agrarian Reform Program (CARP) in the last 30 years using the program's theory of change. A results chain framework was constructed and the program processes examined drawing from several studies that assessed the implementation and impact of CARP. The study notes that the accomplishments of CARP in terms of land-reformed area and number of beneficiaries for the past 30 years have been substantial. However, there is evidence that the program has been poorly targeted in terms of areas covered and beneficiaries. The Department of Agrarian Reform (DAR) experienced difficulty in constructing the land inventory and master list of beneficiaries due to the absence of parcel-based information on land use and ownership and the poor land record system in the country. There is also no inventory of farmers or tenants in the country. Targeting thus has been largely influenced by landowners, local officials, including DAR officials at the local level so as to expedite the process of land tenure improvement.
Keywords: 330; Philippines; CARP; agrarian reform; agrarian reform beneficiaries; Comprehensive Agrarian Reform Program; land reform